Monitoring strategies and key indicators for sustaining the heritage values of Melaka and George Town world heritage cities / Sumarni Binti Ismail - Ismail, Sumarni (2014)

(untitled)
This research has been carried out with the aim to establish a monitoring framework for heritage values of Melaka and George Town. The Operational Guidelines of UNESCO on the management of the World Heritage Site stipulates that all State Parties are required to submit the monitoring report to UNESCO on a 6-years circle, with the objective to evaluate the state of conservation of the inscribed sites. UNESCO has come up with the monitoring format for all State Parties to use, but this format is vague, not specific and general in nature. This research has been carried out with the clear objectives to provide a specific monitoring framework to monitor the Outstanding Universal Values (OUV) of Melaka and George Town, specifically those values under criteria (ii), (iii) and (iv) of the Operational Guidelines. None of the of the inscribed sites has developed such details framework to date. This research is also done to develop key indicators for the monitoring strategies for the stage of conservation of the mentioned properties. Therefore, there is a need to review all international guidelines such as charters, recommendations and resolutions on the conservation of historical town issued by the international agencies such as UNECSO and ICOMOS to develop a framework for monitoring the cultural properties. No doubt, as the capital cities, George Town and Melaka are constantly faces with the issues such as development pressures, mass tourism and also providing facilities for tourist. The management of the cities by the local authority must be made fully aware that the cultural values and the integrity of the sites depend very much on how they care and manage their sites in the long term. Cooperation and partnership between the iv authorities and the private building owners form the basis for a good working relationship that is vital to keep the values of the WHS intact for future generations. This research adopts various approaches of study. The case study and qualitative survey methods are the main strategies for data collection. The Initial framework was developed based on the related literature, as well as the outcome of site visits to the other inscribed sites such as Hoi An, Vietnam and Macau PRC. Face-to-face structured interviews were carried out with the officer in-charge at MBMB and MPPP, as well as professionals in managing the WH sites. It was then refined by focus group meeting in Malacca and later in George Town and also by the local experts. The Draft framework was circulated to the international experts through Delphi method for verification and agreements before being finalized. The research established 11 strategies and 58 indicators for Melaka and George Town. The strategies for urban form and urban fabric include the new developments, restoration works, landscape, infrastructure works (services)/facilities, visual link and cognition (images) and also traffic and circulation and pedestrian. Meanwhile, the strategies for heritage buildings include building’s condition, building under disaster/damage, building use, intervention , and repair, as well as signage.